Endoscopic Removal of an Inadvertently Swallowed Toothbrush in the Emergency Department. (2nd July 2012) - Harvey, Martyn; Cave, Grant; Prince, Gaynor
Abstract : A 16-year-old girl inadvertently swallowed a toothbrush during attempted manual induction of emesis. The 20 cm toothbrush was successfully removed via overtube facilitated endoscopy using a retractable snare while the patient was sedated in the emergency department.